2017
DOI: 10.1155/2017/2157247
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serum Cytokines and Single-Nucleotide Polymorphisms of SOD1, SOD2, and CAT in Erysipelas Patients

Abstract: Increased free radical production had been documented in group A (β-hemolytic) streptococcus infection cases. Comparing 71 erysipelas patients to 55 age-matched healthy individuals, we sought for CAT, SOD1, and SOD2 single polymorphism mutation (SNPs) interactions with erysipelas' predisposition and serum cytokine levels in the acute and recovery phases of erysipelas infection. Whereas female patients had a higher predisposition to erysipelas, male patients were prone to having a facial localization of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…We also confirmed that HGF and SCF increased the expression of mitochondrial-associated proteins, Catalase and SOD2, via activation of the PI3K/AKT and ERK1/2 signaling pathways, which have antiapoptotic roles and regulate the apoptosis-related proteins, Bcl and Bax [38]. HGF and SCF modulated the osteogenic differentiation of MSCs through the ERK1/2 signaling pathway [39,40], effectively promoting the timely removal of excessive ROS in cells, reducing mitochondrial damage, and delaying cellular senescence. In addition, HGF and SCF can promote the self-renewal capacity of MSCs by regulating the expression of the cell cycle-related protein, p21, and the stemness markers, Nanog and OCT4, through the STAT3 pathway [41,42].…”
Section: Discussionsupporting
confidence: 62%
“…We also confirmed that HGF and SCF increased the expression of mitochondrial-associated proteins, Catalase and SOD2, via activation of the PI3K/AKT and ERK1/2 signaling pathways, which have antiapoptotic roles and regulate the apoptosis-related proteins, Bcl and Bax [38]. HGF and SCF modulated the osteogenic differentiation of MSCs through the ERK1/2 signaling pathway [39,40], effectively promoting the timely removal of excessive ROS in cells, reducing mitochondrial damage, and delaying cellular senescence. In addition, HGF and SCF can promote the self-renewal capacity of MSCs by regulating the expression of the cell cycle-related protein, p21, and the stemness markers, Nanog and OCT4, through the STAT3 pathway [41,42].…”
Section: Discussionsupporting
confidence: 62%
“…Our observation, as well as two other reports, suggests that recurrent erysipelas can be considered as inflammatory reactions able to fight invasive infections efficiently in the context of specific host genetic factors. Those observations can be related to published evidence of host factors modulating free radical and cytokine production, and linkage studies in families with recurrent erysipelas …”
mentioning
confidence: 85%
“…Interestingly, other studies also show a connection between HGF and erysipelas, which is a recurrent feature in the affected individuals in this family. It was demonstrated [20] that patients carrying the SOD2 C2734T mutation, which is associated with an increased susceptibility to erysipelas, had lower serum HGF levels compared to those with the wildtype SOD2 gene. This may hint at the link between HGF and erysipelas, but a lot more data is needed to support that link.…”
Section: Identification Of the Hgf Variant In The Familial Lymphedema...mentioning
confidence: 99%